(3cTa GdQjf aj CMhGd GdYjfs - (3eMeO Hf EHQGgje Hf SGYO GdGfUGQj GdSfLGQj, hjYQa HGHf GdCcaGfj, CHh YHO Gddg,J (B749 (3g` s ((3eMeO GHf CMeO Hf Ydi eMeO GdGeGe HLGeY GdcHjQ s)
(3ChdgG (B:s
(3GdMeO ddg GdPi Ndb cd TF HMceJg hHYO aEfi LGeY gPG GdcJGH aj UfGYI GdcMd heQJHg Ydi KdGK ebGdGJ s
(3BNQgG (B:s
(3QHY LRA RgQ HfaSL , KdGKI CLRGA jLeY HYSd eYbhO hdjcf gPG BNQ GdcJGH s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B299 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B200s
(3JHUQGJ GdCUd (B:s
Keywords: (3eJaQbGJs